Phylogenetic analysis and epidemiological history of Hepatitis E virus 3f and 3c in swine and wild boar, Italy. Issue 10 (October 2020) - Lo Presti, Alessandra; Bruni, Roberto; Villano, Umbertina; Marcantonio, Cinzia; Equestre, Michele; Ciuffetelli, Massimo; Grimaldi, Alessandro; Suffredini, Elisabetta; Di Pasquale, Simona; De Medici, Dario; Ciccaglione, Anna Rita
Abstract: Background: Hepatitis E virus (HEV) genotype 3 has a worldwide distribution. The food-borne transmission of HEV associated with the consumption of products derived from domestic pig, wild boar has been reported in various countries. In this study the genetic diversity, evolutionary rates of HEV 3f, 3c among swine and wild boar in Italy were estimated. Methods: Sampling was performed on a wild boar population living in an area located in Abruzzo region. The HEV RNA amplification was performed by real-time RT-PCR. Nested RT-PCR and sequencing of the ORF2 region were carried out by the Super Script III First-Strand Synthesis System. Sequencing of purified PCR products was carried out by the Genome Lab Dye Terminator Cycle Sequencing (DTCS) Quick Start Kit. The maximum likelihood trees were generated by using Phyml. The mean evolutionary rates and the dated trees were co-estimated by BEAST. Results: The phylogenetic analysis showed that the HEV ORF2 isolates from Abruzzo region belonged to 3f subtype. The prevalent subtypes in Italy were those belonging to 3f and 3c. The estimated mean values of the HEV ORF2 capsid gene evolutionary rates were 1.915 × 10 −2 substitutions/site/year (95% HPD: 1.64 × 10 −3 – 3.97 × 10 −2 ) and 2.81 × 10 −2 substitutions/site/year (1.83 × 10 −2 - 3.8 × 10 −2 ) for 3f and 3c subtype datasets, respectively. The HEV 3f dated back to 1985 (1960–2000), whereas the 3c subtype entered in Italy during the year 2006 (2005–2006). The majority of the HEV 3f sequences collected from swine didn't appear intermixed, except in two cases. The HEV 3c population circulating in Italy remained segregated without significant transfer to swine. Conclusion: Our study provide insight into the evolution, circulation of HEV 3f and 3c in Italy. Continued genomic surveillance of HEV in animal reservoir, as well as improving sanitary control measures are required. Abstract : Bioinformatics; Microbiology; Epidemiology; Hepatitis E virus; Molecular evolution; Phylogeny; Animal reservoir; Genomic surveillance.